Nation and Corruption: The Politics of Citizenship in Popular Telugu Cinema - Ramesh, K. Sree (Asian Cinema, 2011)
This article examines the effects of political corruption in India, perceiving it as one of the major detriments for the nation’s growth and a major obstacle to the functioning of democracy and the rule of law, and arguing that its effect on the social fabric of society is the most damaging as it undermines people’s trust in the political system, institutions, and its leadership. This article examines the portrayal of corruption and the alienation of the citizen in recent popular Telugu films, focusing in particular on Bharateeyudu (Shankar, 1996), Tagore (VV. Vinayak, 2003) and Aparichitudu (Shankar, 1996), arguing that corruption, political as well as bureaucratic, has been the sub text if not the main theme of many Telugu films over the decades. It argues that the films are an attempt to reinstate the citizens, the middle class with both their rights and responsibilities, as the bulwark of the polity.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9hYy4yMi4xLjE3MF8x